Kemampuan Resolusi Konflik Interpersonal pada Diri Remaja Setelah Mengikuti Conflict Resolution Outbound Training - Ramadhani, Hetti Sari (Persona:Jurnal Psikologi Indonesia, 2016)
Adolescents development make themprone to conflict. In the juvenile stages happensconfusion between the role of adolescents and the demands of the surrounding community, so itmake adolescents involved in a conflict in their environment. This condition will be difficult whenadolescent do not have the cognitive skills in resolving the conflict. In this study aims to describehow the quality of adolescents in conflict resolution skills after participating in Conflict ResolutionOutbound training. The approach used is a qualitative approach with subjects examined wereparticipants in Basecamp Training TSOT PrigenPasuruan who are following Conflict ResolutionOutbound training. Data collection techniques used were interviews and observation. While thetools used are interview, observation and recording devices. Based on the research adolescents whohave followed Conflict Resolution Outbound Training demonstrate a constructive attitude in dealingwith interpersonal conflicts that they feel has a tremendous spirit (has power and energetic), feelmore able to act and act productive, have the ability to describe the strength of himself and others,find it more valuable to himself, feel closer to other people, and have a greater motivation to buildrelationships with others into a deeper relationship. So Conflict Resolution Outbound Training canimprove interpersonal conflict resolution skills for adolescents.Keywords : Outbound Training, Interpersonal Conflict Resolution, Adolescents